Asian Infrastructure Investment Bank (AIIB) as an Instrument for Regional Leadership of China in the East Asia Region - Anggara Raharyo (AEGIS : Journal of International Relations, 2018)
The establishment of the Asian Infrastructure Investment Bank (AIIB) has sparked many debates and controversies in the last five years since it was announced back in 2013. Amongst studies trying to explain the reason for the establishment of the AIIB, most of them are based on the analysis of Sino-U.S. relations especially on how they overlooked China as a replacement for global hegemon to the U.S.However, considering China’s foreign policy in the recent decade, the establishment of the AIIB is considered as a typical step to becoming a leader in regionalism of East Asia. This writing concludes that China is still only aiming to become regional leader in the scale of East Asia. Keywords: East Asia, Regionalism, Leadership, China, AIIB